European handbook of neurological management : Volume 1 - Gilhus, Nils Erik.; Brainin, M. (Michael); Barnes, Michael P., 1952- (Chichester, West Sussex, UK : Wiley-Blackwell, 2010)
Evidence-based, peer reviewed, best practice management guidelines for neurologists. Diagnosis is only part of the puzzle. Effective treatment is what your patients really want. The European Federation of Neurological Societies has been publishing management guidelines in the European Journal of Neurology for many years. Developed by a consensus approach, using graded evidence, and then fully peer reviewed, these guidelines provide gold-standard, best-practice guidance to the treatment of neurological disorders. They help bridge the gap between what is done and what should be done for patients.
European Handbook of Neurological Management, Volume 1, SECOND EDITION; Contents; Introduction; Section 1: Investigations; Section 2: Major Neurological Diseases; Section 3: Neuromuscular Diseases; Section 4: Infections; Section 5: Neurological Problems; Section 6: Sleep Disorders; Section 7: Rehabilitation; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Nervous system -- Diseases -- Treatment -- Europe -- Handbooks, manuals, etc; Nervous System Diseases; Diseases; Europe; Handbooks, manuals, etc; Nervous system; Nervous system -- Diseases -- Treatment -- Europe; Nervous System Diseases -- therapy; Treatment; Medicine; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Nervous system -- Diseases -- Treatment; Europe; Practice Guideline; Electronic books; Handbooks and manuals